New Method for the Development of Plasmonic Metal-Semiconductor Interface Layer: Polymer Composites with Reduced Energy Band Gap. (7th December 2017) - Aziz, Shujahadeen B.; Mamand, Soran M.; Saed, Salah R.; Abdullah, Ranjdar M.; Hussein, Sarkawt A.
Abstract : Silver nanoparticles within a host polymer of chitosan were synthesized by using in situ method. Ultraviolet-visible spectroscopy was then carried out for the prepared chitosan : silver triflate (CS : AgTf) samples, showing a surface plasmonic resonance (SPR) peak at 420 nm. To prepare polymer composites with reduced energy band gap, different amounts of alumina nanoparticles were incorporated into the CS : AgTf solution. In the present work, the results showed that the reduced silver nanoparticles and their adsorption on wide band gap alumina (Al2 O3 ) particles are an excellent approach for the preparation of polymer composites with small optical band gaps. The optical dielectric loss parameter has been used to determine the band gap experimentally. The physics behind the optical dielectric loss were interpreted from the viewpoint of quantum mechanics. From the quantum-mechanics viewpoint, optical dielectric loss was also found to be a complex equation and required lengthy numerical computation. From the TEM investigation, the adsorption of silver nanoparticles on alumina has been observed. The optical micrograph images showed white spots (silver specks) with different sizes on the surface of the films. The second semicircle in impedance Cole-Cole plots was found and attributed to the silver particles.